SALIM’S NEEDS IN DANNY BOYLE’S SLUMDOG MILLIONAIRE MOVIE: A HUMANISTIC APPROACH - DAROJATUN , FADLI (2006)
The major problem of the study is how are Salim’s needs reflected in Danny Boyle’s Slumdog Millionaire. The objectives of the study are to analyze the movie based on structural analysis and to analyze Salim’s needs in Danny Boyle’s Slumdog Millionaire based on Humanistic Approach.